2022
DOI: 10.3389/fmicb.2022.974432
|View full text |Cite
|
Sign up to set email alerts
|

Classification and molecular characteristics of tet(X)-carrying plasmids in Acinetobacter species

Abstract: The rapid dissemination of plasmid-mediated tet(X) genes in Acinetobacter species has compromised the clinical effectiveness of tigecycline, one of the last-resort antibiotics. However, the classification strategy and homology group of tet(X)-positive Acinetobacter spp. plasmids remain largely unknown. In this study, we classified them by genome-based replicon typing, followed by analyses of structural characteristics, transferability and in vivo effect. A total of 34 plasmids distributed in at least nine Acin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The current extensive use of tetracycline antibiotics has led to the widespread presence of tetracycline resistance genes in gram-negative bacteria, which poses a serious threat to human and animal health ( Zheng et al, 2022 ). The tet X resistance gene family is thought to degrade tetracyclines, and notably this resistance gene family degrades tigecycline, an antibiotic used in recent years to treat MDR bacterial infections in humans and animals ( Chen et al, 2022 ). Recently, Cui et al (2020) reported that tet X resistance genes can be transmitted through plasmids in air and water ( Cui et al, 2020 ), and R. anatipestifer can carry a plasmid pRCAD0416RA1 that mediates tet X resistance genes ( Zhu et al, 2022 ), this suggests that tetracycline resistance in R. anatipestifers may also be mediated by plasmids and this resistance can be transmitted not only among livestock and poultry, but also to humans through a variety of transmission routes, posing a threat to human health.…”
Section: Discussionmentioning
confidence: 99%
“…The current extensive use of tetracycline antibiotics has led to the widespread presence of tetracycline resistance genes in gram-negative bacteria, which poses a serious threat to human and animal health ( Zheng et al, 2022 ). The tet X resistance gene family is thought to degrade tetracyclines, and notably this resistance gene family degrades tigecycline, an antibiotic used in recent years to treat MDR bacterial infections in humans and animals ( Chen et al, 2022 ). Recently, Cui et al (2020) reported that tet X resistance genes can be transmitted through plasmids in air and water ( Cui et al, 2020 ), and R. anatipestifer can carry a plasmid pRCAD0416RA1 that mediates tet X resistance genes ( Zhu et al, 2022 ), this suggests that tetracycline resistance in R. anatipestifers may also be mediated by plasmids and this resistance can be transmitted not only among livestock and poultry, but also to humans through a variety of transmission routes, posing a threat to human health.…”
Section: Discussionmentioning
confidence: 99%
“…GR1 to GR19 are classified based on polymerase chain reaction (PCR) typing for the gene encoding RIPs (Bertini et al., 2010 ). Additionally, GR20 to GR61 have been proposed according to the above typing scheme, with at least 80% nucleotide coverage and at least 75% nucleotide identity of RIP genes in the same group (Castro‐Jaimes et al., 2022 ; Chen et al., 2022 ; Li et al., 2022 ). Notably, the genetic content encompassing RIPs and their adjacent DNA sequences within plasmids of Acinetobacter are similar, implying that some of the plasmids are within the same incompatibility group (Salgado‐Camargo et al., 2020 ).…”
Section: General Features Of Representative Mgesmentioning
confidence: 99%
“…Total DNA is directly extracted from the target environment and used as a template for PCR, allowing the detection of the presence or absence of plasmids based on amplification. Several primer sequences enabling multiplex PCR have been used to detect plasmids that are particularly important in the spread of ARGs (Carattoli, 2009 ; Carattoli et al., 2005 , 2014 ; Carloni et al., 2017 ; Castro‐Jaimes et al., 2022 ; Chen et al., 2022 ; Clewell, 2007 ; Li et al., 2022 ; Lozano et al., 2012 ). PCR‐Southern blot and quantitative PCR analyses using primers or probes specific to plasmid sequences have been used to detect the abundance of specific plasmids and their temporal changes in various environmental samples (Blau et al., 2020 ).…”
Section: Behaviours Of Mges In Natural Environmentsmentioning
confidence: 99%